Science, Technology, Engineering, and Mathematics (STEM) and Research Skill Development (RSD) in Science Education in Higher Education: A Delphi-Based Model - Eli Trisnowati; Wiyanto Wiyanto; Bambang Subali; Sulhadi Sulhadi; Sofina Tamam (ASEAN Journal of Educational Research and Technology, 2027)
This study developed and validated a science learning model integrating Science, Technology, Engineering, and Mathematics (STEM) with the Research Skill Development (RSD) framework to strengthen students’ research skills. A two-round Delphi study was conducted with experts to establish consensus on the model. The first round generated a conceptual synthesis through qualitative thematic analysis, while the second evaluated expert agreement using Aiken’s V. Experts reached strong consensus on the model structure, the central role of science, integration of the engineering design process, contextual problem-based learning, and progressive research stages. The proposed model has high content validity and provides a systematic framework for developing research skills, supporting student independence, and strengthening research-oriented science learning across higher education contexts.